Trends and seasonality of vector borne diseases in Kerala - Raj, Jishnu; V., Soorya; K. R., Anitha (International Journal Of Community Medicine And Public Health, 2022)
Background: Even though epidemiological transition of Kerala is from communicable to non-communicable diseases, re-emerging communicable diseases is a challenge to health service system. Information about disease trends and pattern and seasonal variation is necessary to ensure healthy life. This study aims to find out the trend and pattern in vector borne diseases and its association with seasons. Methods: Study used integrated disease surveillance programme (IDSP) data of vector borne diseases from Directorate of Health Services, Kerala. Seasons are classified as summer, rainy and winter. Mean differences in frequency between two sample proportions (between seasons) were tested using analysis of variance (ANOVA) test. Results: The fluctuations in vector borne disease are mainly due to dengue. Percent share of acute encephalitis syndrome (AES) and Japanese encephalitis (JE) is low but fatality is high among these diseases. Fatality rate for dengue and malaria is low but scrub typhus is high. Thiruvananthapuram is in the first position in reporting these diseases except in 2018, when Malappuram holds the first position. Idukki, Kottayam and Wayanad are the districts with lowest percents. Diseases increase during rainy season. Conclusions: There is necessary monitoring from LSGD and health institutions at primary level to do grass root level sanitation and health awareness to prevent dengue fever. Proper monitoring of entering data from health institutions is needed. The study provides an insight to the vector borne diseases in Kerala which help planning the infrastructure and human resources in public hospitals.